IMPLEMENTATION OF AMTSILATI AS A METHOD OF TEACHING ARABIC AT DARUL FALAH AMTSILATI IN JEPARA AND ALWASILAH LILHASANAH ISLAMIC BOARDING SCHOOLS IN SUKABUMI - Deddy Soe’aiddy, Mochammad (Fakultas Agama Islam dan Pendidikan Guru, 2025)
The emergence of the Arabic language teaching method known as Amtsilati is aimed at improving students' ability to read Arabic texts. In this journal, the author will present the results of the research on the implementation of Amtsilati using the case study method. The results of this study explain that the implementation of Arabic language learning through the Amtsilati method is carried out through practice, meaning assignment, memorization, and word-by-word application in practical classes at the Darul Falah Amtsilati Islamic Boarding School in Jepara and the Alwasilah Lilhasanah Islamic Boarding School in Sukabumi.